Analisis Pengaruh Inflasi, Kurs, dan Suku Bunga Terhadap Harga Saham pada Perbankan Konvensional Yang terdaftar di Bursa Efek Indonesia Tahun 2014-2018 - Jumria jumria (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2020)
ABSTRACTThis study aims to determine the effect of inflation, exchange rates and interest rates on stock prices in conventional banks listed on the Indonesia Stock ExchangeThis study uses a sample of 5 banking service companies listed on the Indonesia Stock Exchange for a period of 5 years ( 2014 – 2018 ). The type of data used is quantitative data, the source of data used is secondary data. The analytical method used is multiple linear regression (multiple regression analysis).The results of the study through the calculation of multiple linear regression obtained inflation has a positive and not significant effect on stock prices in conventional banks listed on the Indonesia Stock Exchange. Exchange rates have a negative and not significant effect on stock prices. Interest rates have a negative and significant effect on stock prices in conventional banks listed on the Indonesia Stock ExchangeKeywords : inflation, exchange rates, interest rates, stock prices.